Normal mitochondrial respiratory function is essential for spatial remote memory in mice - Tanaka, Daisuke (BioMed Central, 2008)
BACKGROUND: Mitochondrial DNA (mtDNA) with pathogenic mutations has been found in patients with cognitive disorders. However, little is known about whether pathogenic mtDNA mutations and the resultant mitochondrial respiration deficiencies contribute to the expression of cognitive alterations, such as impairments of learning and memory. To address this point, we used two groups of trans-mitochondrial mice (mito-mice) with heteroplasmy for wild-type and pathogenically deleted (Δ) mtDNA; the "low" group carried 50% or less ΔmtDNA, and the "high" group carried more than 50% ΔmtDNA. RESULTS: Both groups had normal phenotypes for not only spatial learning, but also memory at short retention delays, indicating that ΔmtDNA load did not affect learning and temporal memory. The high group, however, showed severe impairment of memory at long retention delays. In the visual cortex and dentate gyrus of these mice, we observed mitochondrial respiration deficiencies, and reduced Ca(2+)/calmodulin-dependent kinase II-α (α-CaMKII), a protein important for the establishment of spatial remote memory. CONCLUSION: Our results indicated that normal mitochondrial respiratory function is necessary for retention and consolidation of memory trace; deficiencies in this function due to high loads of pathogenically mutated mtDNA are responsible for the preferential impairment of spatial remote memory.